FRATELLI TUTTI AND IMPLICATIONS ON DEMOCRACY IN AFRICA - Opongo, Elias O. (Asian Horizons, 2020)
The paradoxical reality of the disparities between economic growth in Africa and increased poverty in the continent is a clear reflection of the dysfunctionality of the inherited democratic and economic systems. The new encyclical of Pope Francis, Fratelli Tutti (Brothers All) that came out in October 2020, draws attention to social consciousness on the common responsibility toward building solidarity, social friendship, global citizenship and fraternal economy that respects human dignity and advances integral human development. Like in many parts of the world, democracy in Africa is in a crisis, and politics has largely been sectarian. There are a number of African countries that have subjected democracy to mockery through constitutional coups that create life presidencies or political manipulation of electoral results to remain in power. The persistent disappointment with democratic systems that economically marginalize the majority of the population, making the rich richer and pressing down the poor to poverty, has raised questions on the extent of efficiency levels of democracy. There have been mass demonstrations expressing this discontentment with democracy whether against bad governance, corruption, disenfranchisement of citizen rights, police brutality or economic marginalization of the majority of the population. Pope Francis’ Fratelli Tutti makes a strong appeal on the need to form “social friendship” advanced by fraternal economy that goes beyond individualistic attitudes sustained by parenthesized solidarity. The advancement of democracy in Africa, and the rest of the world, will have to be based on the principles of common good and respect for human dignity, through actualization of democratic systems that respect fair distribution of national resources, care of the poor and marginalization, and creation of employment opportunities, especially for the youth.